#1**0 **

To answer this, you will need to know a property about parallelograms.

The property states: The diagonals of a parallelogram bisect each other.

Bisect: To split into 2 equivalent parts.

We'll put that to the side for now, it will come handy later into this explanation.

We know that...

\(LW = LJ - WJ\)

\(5x + 2 = 11x + 2 - WJ\)

So, what's WJ?

Let's refer back to what we said earlier.

The diagonals of a parallelogram bisect each other.

Now we know that \(LW = WJ\).

We can change our equation to make it solvable.

\(5x + 2 = 11x + 2 - (5x + 2)\)

\(5x + 2 = 11x + 2 - 5x - 2\)

\(5x+2=6x\)

\(x=2\)

Now substitute the value of x into 5x+2.

\(5x+2=5(2)+2\)

\(5x+2=12\)

\(LW = 12\)

And you are done!

Guest Mar 29, 2021